2008
DOI: 10.1167/iovs.07-1474
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Reactivity of Müller Cells after Retinal Detachment in Mice Deficient in GFAP and Vimentin

Abstract: Müller cells are subtly different in the GFAP(-/-)vim(-/-) mouse retina before detachment. The end foot region of these cells may be structurally reinforced by the presence of the intermediate filament cytoskeleton, and our data suggest a critical role for these proteins in Müller cell reaction to retinal detachment and participation in subretinal gliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 39 publications
5
82
0
3
Order By: Relevance
“…For instance, Vim GFAP dKO mice have a high incidence of mortality when subjected to brain injury (9) and retinal Müller glial endfeet are also especially sensitive to physical injury (53). In contrast, we found that pharmacological delivery of 2 mg/kg of WFA causes knockdown of soluble vimentin and GFAP in injury healing WT mice to levels found in uninjured controls, and this WFA dose did not increase fragility of ocular tissues.…”
Section: Discussionmentioning
confidence: 50%
“…For instance, Vim GFAP dKO mice have a high incidence of mortality when subjected to brain injury (9) and retinal Müller glial endfeet are also especially sensitive to physical injury (53). In contrast, we found that pharmacological delivery of 2 mg/kg of WFA causes knockdown of soluble vimentin and GFAP in injury healing WT mice to levels found in uninjured controls, and this WFA dose did not increase fragility of ocular tissues.…”
Section: Discussionmentioning
confidence: 50%
“…GFAP Ϫ/Ϫ Vim Ϫ/Ϫ mice show reduced reactive gliosis and glial scar formation, a slower healing process with increased loss of neuronal synapses after neurotrauma (172,262), and decreased resistance of the CNS tissue to severe mechanical stresses (142,243). While astrocytes around the CNS lesion in GFAP Ϫ/Ϫ Vim Ϫ/Ϫ mice are comparable to those of wild-type mice with respect to their number and the volume they access (262), they do not develop the typical reactive phenotype characterized by the thickening (hypertrophy) of their main cellular processes (260,262) (FIGURE 8, A AND B).…”
Section: Vimmentioning
confidence: 99%
“…The genetic knockouts of IFs, while revealing that they are not essential for development or reproduction (9,10), have drawn more recent attention to their functions in tissue repair and stress response (11,12). Vimentin is the prototypic Type III IF protein that is widely studied because of its involvement in wound healing, fibrosis, angiogenesis, tumor cell differentiation, migration, and metastasis (13)(14)(15)(16)(17)(18). Vimentin plays a critical role in wound repair by providing activated wound fibroblasts during transition to the myofibroblastic phenotype with force generation required for tissue contraction (19).…”
mentioning
confidence: 99%